2020
DOI: 10.1002/app.49232
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silk fibroin nanoparticles on the morphology, rheology, dynamic mechanical properties, and toughness of poly(lactic acid)/poly(ε‐caprolactone) nanocomposite

Abstract: The silk fibroin nanoparticles (SFNPs) were extracted from silkworm cocoons and used as a nanofiller in poly(lactic acid) (PLA)/poly(ε‐caprolactone) (PCL) blend. The nanoparticle localization was studied theoretically and experimentally and the effects of SFNP on the morphology, rheology, toughness, and dynamic mechanical properties of the blend were investigated. According to the calculated wetting coefficient, SFNP should be thermodynamically located in the PLA matrix during the melting process. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…The practicality of understanding the viscoelastic behavior is foremost necessary for evaluating melt processing factors, dispersion, and the interfacial interaction of the fibers in the matrix, as well as the morphological aspects of various phases in the composites (filler and matrix), especially when working on 3D printing . A uniform dispersion of microfibers in the polymer matrix can impact the melt rheology of the composites . The viscoelastic behavior was reproducible despite repetitive melt–cooling cycles, suggesting even dispersion and stability of the silk fibroin microfibers in the PCL matrix with no signs of material degradation prompted by the temperature cycling as seen in other studies .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The practicality of understanding the viscoelastic behavior is foremost necessary for evaluating melt processing factors, dispersion, and the interfacial interaction of the fibers in the matrix, as well as the morphological aspects of various phases in the composites (filler and matrix), especially when working on 3D printing . A uniform dispersion of microfibers in the polymer matrix can impact the melt rheology of the composites . The viscoelastic behavior was reproducible despite repetitive melt–cooling cycles, suggesting even dispersion and stability of the silk fibroin microfibers in the PCL matrix with no signs of material degradation prompted by the temperature cycling as seen in other studies .…”
Section: Discussionsupporting
confidence: 81%
“…19 A uniform dispersion of microfibers in the polymer matrix can impact the melt rheology of the composites. 20 The viscoelastic behavior was reproducible despite repetitive melt−cooling cycles, suggesting even dispersion and stability of the silk fibroin microfibers in the PCL matrix with no signs of material degradation prompted by the temperature cycling as seen in other studies. 11 Our study demonstrated that with the increase in the silk content the storage and the loss moduli increased compared to those of PCL alone (Figure 1), and this has been shown in various PCL based composites with clay, 21 hydroxyapatite, and tricalcium phosphate.…”
Section: Discussionsupporting
confidence: 64%
“…The scaffolds with an excellent arrangement of porous structure might have well mechanical attributes which have a direct impact on their clinical efficient (Xu et al 2015). The presence of fibroin in the present scaffold has improved the mechanical properties as mentioned in many studies (Chen et al 2019;Dadras Chomachayi et al 2020;Eivazzadeh-Keihan et al 2021). In addition, the opposite charge balance between silk fibroin and gelatin and the presence of the high content of hydrophilic amino acids of SF can affect the compression modulus (Lu et al 2010;Si et al 2011).…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, cellulose nanofibers/whiskers (CNF) derived from renewable biomass are currently attracting research attention because they portray great potential in reinforcing PLA 121‐123 . However, a list of challenges prevents their usage.…”
Section: Role Of Nanoparticles In Poly(lactic Acid)mentioning
confidence: 99%